2016
DOI: 10.1016/j.cell.2016.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantification of Matrix Metabolites Reveals the Dynamics of Mitochondrial Metabolism

Abstract: SUMMARY Mitochondria house metabolic pathways that impact most aspects of cellular physiology. While metabolite profiling by mass spectrometry is widely applied at the whole-cell level, it is not routinely possible to measure the concentrations of small molecules in mammalian organelles. We describe a method for the rapid and specific isolation of mitochondria, which we use in tandem with a database of predicted mitochondrial metabolites (“MITObolome”) to measure the matrix concentrations of greater than 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
377
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 401 publications
(401 citation statements)
references
References 50 publications
11
377
1
Order By: Relevance
“…During the purification procedure, alterations in NAD + and NADH concentrations are expected. This limitation was recently overcome, at least in part, by leveraging affinity-tag-based purification of mitochondrial organelles, prior to metabolite extraction and analysis by liquid chromatography-tandem mass spectrometry (LC-MS/MS) [20]. In line with earlier findings, this study reported a total mitochondrial NAD + concentration of 818 μM and an NAD + /NADH ratio of 111.…”
Section: Physiological Concentrations and States Of Nad+ In Vivosupporting
confidence: 74%
“…During the purification procedure, alterations in NAD + and NADH concentrations are expected. This limitation was recently overcome, at least in part, by leveraging affinity-tag-based purification of mitochondrial organelles, prior to metabolite extraction and analysis by liquid chromatography-tandem mass spectrometry (LC-MS/MS) [20]. In line with earlier findings, this study reported a total mitochondrial NAD + concentration of 818 μM and an NAD + /NADH ratio of 111.…”
Section: Physiological Concentrations and States Of Nad+ In Vivosupporting
confidence: 74%
“…Possibly, other thiol-containing molecules, such as GSH could serve as the acetyl group acceptor, considering that the cellular CoA is around 10 µM while GSH is 1 to 7 mM (Fig. 3b), and similar concentration values in different types of cells or tissues were also reported by others [28][29][30] . Low levels of CoA and high levels of GSH were also observed in autochthonous mouse tumors providing a physiological context for this occurrence (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Isolation of subcellular organelles can unfortunately perturb metabolite concentrations: There is no validated method to quench metabolic activity without causing leakage between compartments. Faster organelle isolation can help mitigate such problems, but the current standard for fast isolation of ~10 min remains slow relative to turnover of many metabolites (141143). Nevertheless, some biological insights may be obtained, although it is important to validate their accuracy.…”
Section: Discussionmentioning
confidence: 99%